62 MYOCARDIAL WORK IN CARDIAC AMYLOIDOSIS AND HYPERTENSIVE HEART DISEASE: A PRELIMINARY REPORT. (15th December 2022) - Trimarchi, Giancarlo; Campisi, Mariapaola; Luongo, Alfredo; De Sarro, Rosalba; Poleggi, Cristina; Lofrumento, Francesca; Licordari, Roberto; Mancinelli, Anna; Dattilo, Giuseppe; Recupero, Antonino; Zito, Concetta; Carerj, Scipione; et al.
Abstract: Objective: Assessment of myocardial work (MW) by pressure-strain loops is a recently introduced ultrasound-based technique allowing a noninvasive estimation of left ventricular (LV) myocardial performance, in a more precise fashion than ejection fraction (LVEF) and global longitudinal strain (GLS). Early studies have shown that MW clusters, such as efficiency (MWE), global wasted work (GWW), global constructive work (GCW) and myocardial work index (MWI) are likely to impair in most patients with hypertrophic heart. These markers can be predictive of myocardial dysfunction from the early stages of the disease and a trend towards fibrosis. To date, there are only scanty information about MW analysis in patients with heart failure (HF) and preserved/mildly reduced left ventricular ejection fraction (LVEF), as in those with cardiac transthyretin amyloidosis (ATTR). This pilot study aimed at evaluating differential MW features in aTTRCA vs hypertensive patients. Methods: 26 male patients, 13 affected by ATTR wild-type (mean aged 74±6 years) and 13 with hypertensive heart disease (HHD, mean aged 63±8 years), were investigated by transthoracic speckle-tracking strain ultrasound. Offline pressure-strain loop analysis was performed by a dedicated software. LV mass index (LVMI), LVEF, GLS, MWE, GWW, GCW and MWI were recognized. Results: Main findings are reported in Table underneath, and the reference MW values provided by the European multi-centre NORRE study* are also displayed. As expected, ATTR patients showed greater LVMI and lower LVEF than those with HHD. MW indices were almost all impaired in ATTR patients, whereas they were in the lower range of normality in the HHD group. Noteworthy, all patients showed normal GWW values, indicative of a complex pathophysiology conveying different HF settings. Conclusions: Findings from this hypothesis generating research indicate that MW is significantly impaired in ATTR compared to HHD patients, whose values, however, were in the low range of normality. Global wasted work was the sole marker to be normal in both groups, suggesting further studies still needed to shed lights on the intricate pathophysiology of myocardial function in cardiac amyloidosis.